PROFIL LIPID PADA PEGAWAI SEKRETARIAT DAERAH (SEKDA) PROVINSI RIAU TAHUN 2012 - Qodri Alfi; Huriatul Masdar Masdar; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Regional Secretariat employees of Riau Province is a part of the community groups working that have some risk factors of the occurrence of dislipidemia. Their job allows the occurrence of changes in lifestyle such as unhealthy sedentary life style, lack of time to do physical activities, consume fast food and a lot of fat, sugar and salt as well as having a higher risk of stress. The purpose of this research is to find out the lipid profile on Regional Secretariat employees of Riau Province. This research uses the descriptive design with cross sectional approach. By the consecutive sampling method obtained 44 samples, one of them dropped out. The research results obtained 62.78% had normal total cholesterol levels, 30.2% had normal LDLcholesterol levels, 62.8% had normal levels of HDL cholesterol and 86.03% had normal triglyceride levels. However, only 11.6% of the total sample research had normal value from the fourth components of lipid. From the results it can be concluded that 88.4% of respondents experienced dislipidemia, although there is only one of the fourth lipid components is abnormal.Key words :lipid profile, Regional Secretariat employees of Riau Province, LDL cholesterol, dyslipidemia